Quantum interferometric metrology with entangled photons - Chen, Yuanyuan; Hong, Ling; Chen, Lixiang (Frontiers in Physics, 2022)
Quantum interferences of entangled photons have engendered tremendous intriguing phenomena that lack any counterpart in classical physics. Hitherto, owing to the salient properties of quantum optics, quantum interference has been widely studied and provides useful tools that ultimately broaden the path towards ultra-sensitive quantum metrology, ranging from sub-shot-noise quantum sensing to high-resolution optical spectroscopy. In particular, quantum interferometric metrology is an essential requisite for extracting the information about the structure and dynamics of photon-sensitive biological and chemical molecules. This article reviews both the theoretical and experimental progresses of this quantum interferometric metrology technology along with their advanced applications. The scope of this review includes Hong-Ou-Mandel interferometry with ultrahigh timing resolution, entanglement-assisted absorption spectroscopy based on a Fourier transform, virtual-state spectroscopy by using tunable energy-time entangled photons.